The efficacy of gradual reduction using two-stage traction for developmental dysplasia of the hip in southern China - Chen, Hui; Wang, Xiang-xuan; Chen, Zhao; Ge, Yihua (Frontiers in Pediatrics, 2024)
Purpose: To report the preliminary outcome of gradual reduction (GR) utilizing two-stage traction (TST) compared with traditional traction (TT) in the treatment of developmental dysplasia of the hip (DDH). Try to evaluate if the prognosis of the TST is better than TT. Methods: The following information was collected on children with DDH who were treated with GR using two-stage traction or traditional traction between June 2016 and August 2017: sex, age, weight, acetabular index (AI), International Hip Dysplasia Institute (IHDI) classification, femoral head ossification, traction time, reduction quality, and labrum shape in arthrography. The AI, IHDI grade, second operation rate, and incidence of femoral head avascular necrosis (AVN) were analyzed after the final comprehensive one-year follow-up. Results: There were 27 cases (31 hips: 18 left, and 13 right) enrolled in this study. 18 hips (16 cases) were assigned to the TT group and 13 hips (11 cases) were assigned to the TST group, with the average diagnosed age of 5.56 ± 1.66 mons and 4.06 ± 1 mons, respectively (p<0.001). The average operation age was 6.01 ± 1.67 and 65 ± 0.86 mons, respectively (p=0.435); the affected left and right sides were 10/8 and 8/5 hips, respectively (p=1); the average age of the initial AI was 37.11 ± 3.26 and 36.77 ± 4.34 (p=0.804). IHDI classification III and IV were 15/3 and 11/2 hips (p=1). The femoral head ossification was present in 6/18 and 2/13 hips (p=0.412). The total traction time was 13.22 ± 2.6 and 49.23 ± 25.77 days, respectively (p<0.001); The IHDI classifications III and IV were 9/9 and 12/1 hips, respectively, after GT (p= 0.02); the AVN was present in 5/18 and 0/13 hips, respectively (p=0.048), the second operation was approved in 5/18 and 1/13 hips, respectively (p=0.359) at final follow-up. Conclusions: Two-stage traction can significantly decrease the IHDI classifications III and IV ratios and the AVN compared to traditional traction, and significantly reduce the total traction time.